Cardiovascular Disease: The Other Face of Diabetes. (23rd October 2013) - Vlasakakis, G; Della Pasqua, O
Abstract : Despite glycemic control, evidence suggests that mortality and morbidity remain high in diabetes. Regulatory agencies deem, therefore, additional safety trials necessary for the approval of new antidiabetic drugs. Nevertheless, markers of cardiovascular risk, which can be used as response predictors, are not available. In contrast with current efforts on further understanding of glucose–insulin homeostasis, a model‐based approach is required to assess the correlation between hyperglycemia and cardiometabolic phenotypes, enabling prediction of the underlying cardiovascular risk. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e81; doi:10.1038/psp.2013.57 ; advance online publication 23 October 2013